2023
DOI: 10.3390/foods12122407
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions and Metabolite Profiling of Grape Juice Fermented with Lactic Acid Bacteria for Improved Flavor and Bioactivity

Dilinu Kuerban,
Jing Lu,
Zekun Huangfu
et al.

Abstract: To enrich the flavor compounds and retain the content of polyphenolics in grape juice (GJ) under long-term storage, Lactiplantibacillus plantarum, Lactobacillus acidophilus, Lacticaseibacillus casei, and Lacticaseibacillus paracasei, were screened and the optimal fermentation conditions were determined as fermentation temperature of 41.2 °C for 24 h with an initial LAB density of 8.5 × 106 CFU/mL. Surprisingly, the retention rates of TPC still remained at 50% after storage for 45 days at 4 °C. Moreover, 251 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The content of vanillic acid and arbutin in fermented pear juice of Lactobacillus plantarum 90 and Lactobacillus casei 37 increased, and the DPPH ability to scavenge free radicals was stronger. ( Kuerban et al, 2023 ; Mirmohammadi et al, 2021) fermented grape juice with Lactobacillus plantarum and Lactobacillus brevis at a ratio of 1:2, and the results showed that mixed bacterial fermentation could enrich phenolic compounds, enhance antioxidant capacity the grape juice has a characteristic aroma and a pleasant flavor. ( Fonseca et al, 2021 ) explored the fermentation of bergamot juice by single and complex strains, and the results showed that the pH value, glucose and fructose consumption, lactic acid and formic acid generation, citric acid consumption and DPPH radical scavenging effect of fermented bergamot juice are affected by complex strains were significantly improved compared to fermentation of single strains.…”
Section: Fermentation Techniques For Elevating the Quality Of Fruit A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The content of vanillic acid and arbutin in fermented pear juice of Lactobacillus plantarum 90 and Lactobacillus casei 37 increased, and the DPPH ability to scavenge free radicals was stronger. ( Kuerban et al, 2023 ; Mirmohammadi et al, 2021) fermented grape juice with Lactobacillus plantarum and Lactobacillus brevis at a ratio of 1:2, and the results showed that mixed bacterial fermentation could enrich phenolic compounds, enhance antioxidant capacity the grape juice has a characteristic aroma and a pleasant flavor. ( Fonseca et al, 2021 ) explored the fermentation of bergamot juice by single and complex strains, and the results showed that the pH value, glucose and fructose consumption, lactic acid and formic acid generation, citric acid consumption and DPPH radical scavenging effect of fermented bergamot juice are affected by complex strains were significantly improved compared to fermentation of single strains.…”
Section: Fermentation Techniques For Elevating the Quality Of Fruit A...mentioning
confidence: 99%
“…( Fonseca et al, 2021 ) explored the fermentation of bergamot juice by single and complex strains, and the results showed that the pH value, glucose and fructose consumption, lactic acid and formic acid generation, citric acid consumption and DPPH radical scavenging effect of fermented bergamot juice are affected by complex strains were significantly improved compared to fermentation of single strains. ( Kuerban et al, 2023 ), It is shown that composite fermentation of fruit and vegetable products can not only enrich nutrients, and improve the flavor, however also promote functional activity. Fermentation of complex strains mainly involves asymbiosis or interaction between different strains and its metabolic mechanism is more complex than that of single strain fermentation, and the fermentation products are more abundant.…”
Section: Fermentation Techniques For Elevating the Quality Of Fruit A...mentioning
confidence: 99%